Justice for Nicaragua from Exile: Denouncing Illegality, Exposing Judicial Shams to Sow - Monte Casablanca, Antonio (2024)
Gonzalo Carrión Maradiaga is a Human Rights lawyer, a profession he has practiced for more than thirty years. He is currently part of the coordination team of the Human Rights Collective Nicaragua Nunca Más, an institution that operates from Costa Rica, due to the repression and political persecution of the Nicaraguan government against organizations or associations related to the defense and promotion of human rights. On September 5, 2023 we had the opportunity to talk at the facilities of the Collective, located in San Pedro. There, we discussed the political trials in Nicaragua, their staging and the authoritarian evolution of the government in that country.